Assessment of the Knowledge, Attitude, and Perception (KAP) of Sheep Farmers Regarding Ticks and Tick-Borne Pathogens in Tunisia, North Africa - Médiha Khamassi Khbou; Syrine Rekik; Rihab Romdhane; Limam Sassi; Felicitas Bergmann; Martin H. Groschup; Mourad Rekik; Mohamed Gharbi (Veterinary Sciences)
Ticks and tick-borne pathogens (TBPs) are a threat to human and animal health worldwide. A structured questionnaire was used to assess the knowledge, attitudes/practices, and perceptions (KAP) of 86 farmers of extensive sheep farming systems across different agro-ecological areas in Tunisia. The response rate was about 91.3%. Overall, 68.5% of the questions referring to knowledge and perceptions were answered correctly. Indeed, about half of the respondents were aware that ticks infest animals, with weight loss given as the major consequence. However, more than half of the farmers were unaware of the transmission and vectorial role of ticks. Those who knew that ticks are vectors cited microbes and icterus as the main concerns. A broad majority of farmers (70.9%) stated that they removed the attached ticks manually and 45.3% crushed them. As acaricides were perceived to be efficient for fighting ticks, according to 97.7% of the sheep farmers, they were used for both the animals and their sleeping areas. Although the toxicity of acaricides is known, 59.3% of the respondents did not use personal protection equipment when applying these products. Taken together, gaps in KAP among sheep farmers were identified. It can be used to better design awareness communication tools for TBPs.